Assessment criteria of the feasibility of replacement standard efficiency electric motors with high-efficiency motors (2021)
Currently, the feasibility to replace standard efficiency electric motors with higher efficiency ones is assessed with considerations differing from real operating conditions in the industry. This study compares the feasibility of replacing 26 standard efficiency motors (IE1) with high-efficiency efficiency ones (IE2 and IE3) in a sugar plant, based on three different energy scenarios and considering the incremental costs or depreciated costs of motors. Energy scenario 1 consider that motors operate for 6000 h/year at full load and nominal efficiency. While scenarios 2 and 3 consider the measured operating time and the load factor of motors. The results show that scenario 1 overestimates electricity consumption between 2 and 18 times, contrasted with a difference of 1e7% in scenarios 2 and 3, leading to saving potentials in scenario 1 between 1.2 and 33.4 times higher than for scenarios 2 and 3. Considering the incremental costs in scenario 1, it is feasibly to replace all the motors in the plant, while it is only feasibly to replace three motors in scenarios 2 and 3 with the depreciated costs. Therefore, the use of scenario 1 based on unrealistic conditions and leading to economic loss, should be avoided in future studies.